1997
DOI: 10.1002/aic.690431328
|View full text |Cite
|
Sign up to set email alerts
|

Intrazeolite nanocomposite catalysts: Co-Mo Sulfides for Hydrodesulfurization

Abstract: It was, for the first time, demonstrated by means of FTIR, EXAFS, XPS

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 36 publications
(53 reference statements)
1
10
0
Order By: Relevance
“…These results suggest that the HYD of butadiene occurs on the Co sites of the Co _ Mo binary sulfide catalyst at Co/Mo = 1 and that the Co sites are important in the HDS reaction. In agreement with the catalytic results, the Fourier transform infrared (FTIR) spectra of NO adsorption on CoSx _ MoSx/NaY 79), 96) showed that NO molecules are adsorbed exclusively on Co sites, forming dinitrosyl species, in spite of the presence of the equal amounts of Co and Mo atoms in the zeolite (2Co + 2Mo/SC). These findings suggest the formation of Co _ Mo mixed sulfides in the zeolite pores rather than a physical mixture of highly dispersed Co and Mo sulfide clusters.…”
Section: Intrazeolite Co-mo Sulfide Clusterssupporting
confidence: 71%
See 4 more Smart Citations
“…These results suggest that the HYD of butadiene occurs on the Co sites of the Co _ Mo binary sulfide catalyst at Co/Mo = 1 and that the Co sites are important in the HDS reaction. In agreement with the catalytic results, the Fourier transform infrared (FTIR) spectra of NO adsorption on CoSx _ MoSx/NaY 79), 96) showed that NO molecules are adsorbed exclusively on Co sites, forming dinitrosyl species, in spite of the presence of the equal amounts of Co and Mo atoms in the zeolite (2Co + 2Mo/SC). These findings suggest the formation of Co _ Mo mixed sulfides in the zeolite pores rather than a physical mixture of highly dispersed Co and Mo sulfide clusters.…”
Section: Intrazeolite Co-mo Sulfide Clusterssupporting
confidence: 71%
“…The catalytic activity of MoSx/NaY for the HDS of thiophene was 3-4 times greater than that of MoS2/ NaY 72), 78) . The activity of MoSx/NaY linearly increased up to 2Mo/SC as the Mo loading increased, followed by a more gradual increase with further addition of Mo 72),78), 96) . This suggests that the same Mo sulfide dimer species are prepared using Mo(CO)6 regardless of the number of Mo(CO)6 molecules in the supercage, if the Mo content is lower than 2Mo/SC.…”
Section: Intrazeolite Mo Sulfide Clustersmentioning
confidence: 94%
See 3 more Smart Citations